On a Shallow Water Model for the Simulation of Turbidity Currents (Communications in Computational Physics, 2009)
We present a model for hyperpycnal plumes or turbidity currents that takesinto account the interaction between the turbidity current and the bottom, consideringdeposition and erosion effects as well as solid transport of particles at the bed loaddue to the current. Water entrainment from the ambient water in which the turbiditycurrent plunges is also considered. Motion of ambient water is neglected and the rigidlid assumption is considered. The model is obtained as a depth-average system ofequations under the shallow water hypothesis describing the balance of fluid mass,sediment mass and mean flow. The character of the system is analyzed and numericalsimulations are carried out using finite volume schemes and path-conservative Roeschemes.